2021
DOI: 10.3390/v13040650
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Antiviral Activity of 3D8, a Nucleic Acid-Hydrolyzing Single-Chain Variable Fragment (scFv), Targeting SARS-CoV-2 and Multiple Coronaviruses In Vitro

Abstract: The virus behind the current pandemic, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the etiology of novel coronavirus disease (COVID-19) and poses a critical public health threat worldwide. Effective therapeutics and vaccines against multiple coronaviruses remain unavailable. Single-chain variable fragment (scFv), a recombinant antibody, exhibits broad-spectrum antiviral activity against DNA and RNA viruses owing to its nucleic acid-hydrolyzing property. The antiviral activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“… 1 ) This type of study has increased worldwide, and many interesting reports have been published in the USA, 14 , 40 43 ) Europe, 44 51 ) and Africa/Asia. 52 54 ) The catalytic antibody has potential in future applications due to its high catalytic activity to cleave the peptide bond of targeting peptides, as well as proteins. In addition, it can cleave DNA (or RNA), which can lead to the suppression of viral infection.…”
Section: Conclusion Opinions and Prospectsmentioning
confidence: 99%
“… 1 ) This type of study has increased worldwide, and many interesting reports have been published in the USA, 14 , 40 43 ) Europe, 44 51 ) and Africa/Asia. 52 54 ) The catalytic antibody has potential in future applications due to its high catalytic activity to cleave the peptide bond of targeting peptides, as well as proteins. In addition, it can cleave DNA (or RNA), which can lead to the suppression of viral infection.…”
Section: Conclusion Opinions and Prospectsmentioning
confidence: 99%
“…Single-stranded variable fragment (scFv) is a catalytic antibody with broad-spectrum antiviral activity against DNA and RNA viruses due to its nucleic acid hydrolysis properties. Lee evaluated the antiviral activity of the scFv 3D8 against SARS-CoV-2 and other coronaviruses in VeroE6 cell culture [ 160 ]. It was found that 3D8 inhibited the replication of SARS-CoV-2, human coronavirus OC43 (HCoV-OC43) and porcine epidemic diarrhea virus (PEDV).…”
Section: Catalytic Antibodies That Inhibit New Coronavirus Infectionmentioning
confidence: 99%
“…The preventive and therapeutic effects of catalytic antibody 3D8 against SARS-CoV-2 in VeroE6 cells were demonstrated. Immunoblotting and plaque analysis showed that the nucleoprotein and infected particles of coronavirus decreased in the cells treated with 3D8 [ 160 ]. These data indicate that 3D8 has broad-spectrum antiviral activity against SARS-CoV-2 and other coronaviruses [ 160 ].…”
Section: Catalytic Antibodies That Inhibit New Coronavirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 3D8 scFv has intrinsic nucleic acid hydrolyzing activity in a sequence independent manner [ 26 ]. Many previous studies have identified 3D8 scFv antiviral effect against IAV, the classic swine fever virus, human herpes simplex virus, pseudorabies virus, and multiple corona viruses [ 26 , 27 , 28 , 29 , 30 ]. While other flu drugs directed to the protein level (e.g, Oseltamivir) were ineffective on the drug resistant strains, alternative antiviral drugs have been developed to replace Oseltamivir.…”
Section: Introductionmentioning
confidence: 99%